PERAN MAKAN SIANG GRATIS DALAM JANJI KAMPANYE PRABOWO GIBRAN DAN REALISASINYA - Maharani, Putri Ardelia; Namira, Alliya Riyani; Chairunnisa, Tsalsabillah Viony (Journal Of Law And Social Society, 2024)
The ‘Free Lunch Program’ that was promised by Prabowo Subianto and Gibran Rakabuming Raka in their Indonesia’s 2024 presidential election campaign has sparked many controversies and uncertainties amongst the general crowd. In this context, this article will explore several controversial aspects of the program, including large financial challenge, its potential impact on the natural resources, fairness in its distribution, and the worry that this will be nothing more than a mere bluff. The large financial challenge comes from the allocation of the budget for this program, which causes questions on its long term longetivity. Other than that, the impact this program will have on the natural resources, especially in terms of the increasing food demand and its pressure towards our soil and water sources, also causes concerns about the sustainability of nature. The matter of whether it will be distributed evenly is also a matter of concern, with the fear that it won’t reach those who are actually in need. Additionally, the concern of this program being nothing more than a political bluff without any intentions of actually implementing it will also hinder its success. In facing those controversies and uncertainities, it’s important for the government to present a clear and effective plan to implement it, as wll as showing the much needed commitment in running the program properly. With that, this Free Lunch Program kan become an important instrument in increasing the people of Indonesia’s well-being, especially for those who are in need.